Microempreendedorismo e microcrédito: utilização da conjoint analysis para análise da percepção de preferência de consumo de microcrédito pelos microempreendedores - Costa, Marcos Vinícius Azevedo da (2016)
Microcredit has been used as a way to encourage small entrepreneurs to make grow their business, and the offering of these small loans has increased a lot in the last 15 years mainly because of legal frameworks and public policies that have developed this financial mechanism. In this area the appearance of the legal figure of the Microemprendedor Individual (MEI) in a context of formalization of informal microentrepreneurs proved to be a classic case of opportunity for the development of supply-oriented productive microcredit. Several microfinance products have been offered to microentrepreneurs, but it is not clear what are the preferences of entrepreneurs by differents microcredits products. This work contributes to this knowledge by presenting a conjoint analysis that reveals microentrpreneurs’ preferences for a number of relevant features of microcredit programs. Therefore aim to make a journey through the development and expansion of credit to microentrepreneurs market, focusing especially on their perception of microcredit features.